Case report: direct suture repair of inferior vena cava to rescue a stab patient with hepatic and caval injury through left hepatectomy and total vascular exclusion - Reina Hirooka; Kyoji Ito; Nobuyuki Takemura; Fuminori Mihara; Norihiro Kokudo (Surgical Case Reports)
Abstract Background The mortality of abdominal vena caval injuries is as high as 50–80%. Yet, there were few reports on how to repair injured inferior vena cava (IVC). This report presents a method of vena caval repair in a case of penetrating retrohepatic IVC injury, requiring hepatic resection and total vascular exclusion (TVE). Case presentation The patient was a 20-year-old man with a stab wound in the epigastrium. An emergency laparotomy was performed in the emergency room, and a stab incision on the left liver was detected. As the Pringle’s maneuver did not reduce bleeding, hepatic vein injury was suspected, and left hemihepatectomy was performed to confirm the bleeding point. After the hepatectomy, laceration was still evident deeper into the resection, and IVC injury was suspected. The bleeding was temporarily controlled by tentative hepatorrhaphy and gauze packing, and the initial damage control surgery was terminated. Definitive surgery was performed on the third postoperative day. The lacerated point was observed under TVE, and the laceration penetrated the retrohepatic IVC through its posterior wall. The slit of the posterior wall was sutured first, followed by suturing of the anterior wall of the IVC. Finally, the lacerated liver was closed with hepatorrhaphy. TVE was removed, and the massive bleeding was successfully controlled. Conclusion In severe liver injuries involving the retrohepatic IVC, hepatic resection and TVE may be useful for ensuring an optimized surgical field for repairing the injured IVC.